Developing Picture Describe For Elementary School Students' Speaking Skills - Abdullah Farih; Afifa Eka Kurniawati Dewi (Belantika Pendidikan, 2021)
The main purpose of this study is to help the English teachers easily to teach speaking in teaching English by describing picture. The activities are consists of reading, listening and talking. The researcher employed Research and Development method (RD) and adapted Borg and Galls’ model which consisted of five stages, namely 1) research and information collection, 2) planning, 3) develop preliminary form of product, 4) preliminary field of testing, and 5) main product revision. The researcher used three instruments to obtain the data such as interview, questionnaires and observation checklist. The obtained data will be classified based on the instrument used. The researcher shows the result by explaining them in quantitative and qualitative approach. The students needed supporting book in learning English that has attractive and colourful picture for students. The product is a describing picture book for elementary school entitled PICRIBE. The result of expert validation of the book is percentage of 4,0% and 4,5% is the result of expert validation ofthe materials. It means the bookis feasible as supporting media in learning speaking